2014
DOI: 10.1021/ci500425y
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches Elucidate the Allosteric Mechanism of Human Aromatase Inhibition: A Novel Possible Route to Small-Molecule Regulation of CYP450s Activities?

Abstract: Human aromatase (HA) is a P450 cytochrome (CYP) with an essential role in estrogen biosynthesis. Since more than 70% of breast cancers are positive for estrogenic receptor (ER), the reduction of estrogen physiological concentrations through HA inhibition is one of most important therapeutic strategies against this cancer type. Recently, experimental evidence showed that selected taxmoxifen metabolites, which are typically used as estrogen receptor modulators (SERMs), inhibit HA through an allosteric mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 83 publications
4
44
0
Order By: Relevance
“…An equilibrated HA model was taken from our previous work, and, by using the CHARMMGUI webserver, it was embedded in a 1‐palmitoyl‐2‐oleoyl‐ sn ‐glycero‐3‐phosphocholine (POPC) membrane containing 6 wt % cholesterol, as reported for the composition of the endoplasmic reticulum membrane . Physiological protonation states were calculated with the webserver H ++ .…”
Section: Methodsmentioning
confidence: 99%
“…An equilibrated HA model was taken from our previous work, and, by using the CHARMMGUI webserver, it was embedded in a 1‐palmitoyl‐2‐oleoyl‐ sn ‐glycero‐3‐phosphocholine (POPC) membrane containing 6 wt % cholesterol, as reported for the composition of the endoplasmic reticulum membrane . Physiological protonation states were calculated with the webserver H ++ .…”
Section: Methodsmentioning
confidence: 99%
“…41,48 In recent times, the aromatase inhibition has been studied by means of different computational techniques, where several AIs have been tested. 10,43,51,[53][54][55][56][57] In this paper, we have focused in particular on the EXE compound (6-methylene-androsta-1,4-diene-3,17-dione) because of the resemblance it has with the natural substrate ASD (androst-4-ene-3,17-dione). EXE shares the steroidal backbone with ASD, however, the main differences that exist between them are: i) a C 6 -substitued methylidene group located at the B-ring of EXE, and ii) a double bond between C 1 and C 2 carbons which is present at the A-ring of the EXE but not in the ASD (see Scheme 3 for comparison).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that 70% of BC cases diagnosed after menopause are Estrogen Receptor (ER) positive (ER+). The human aromatase (HA) enzyme produces estrogens (17-ÎČ-estradiol or estrone) (Magistrato et al, 2017) mainly after menopause, and its inactivity increases the level of estrogens in malignant tissues (Liang and Shang, 2013;Sgrignani et al, 2014Sgrignani et al, , 2015Sgrignani et al, , 2016Magistrato et al, 2017). These hormones have a pro-oncogenic effect by either stimulating cell proliferation or decreasing apoptosis when binding to ERα as an agonist (Liang and Shang, 2013).…”
Section: Introductionmentioning
confidence: 99%